1989
DOI: 10.1159/000293607
|View full text |Cite
|
Sign up to set email alerts
|

Group B Streptococcus and Premature Rupture of Membranes and Preterm Delivery

Abstract: In a population of 1,050 pregnant women the effect of maternal colonization by group B Streptococcus on premature rupture of membranes (PROM), preterm delivery, and low weight was analyzed. A significant increment was found of the prevalence of PROM for patients colonized in the vagina and/or the rectum (26.4%) versus noncarrier patients (17.8%). In vaginal and/or rectal group B Streptococcus carriers, in whom group B Streptococcus was also isolated from the cervical culture, the rate of PROM was higher (41.7%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…2,3 Although the majority of pregnant women remain asymptomatic, GBS colonization has been linked to certain obstetric complications, including chorioamnionitis and premature rupture of membranes. 4,5 Vertical transmission of maternal GBS is a leading cause of neonatal sepsis, pneumonia, and meningitis. Randomized clinical trials in the 1980s showed that intrapartum antibiotic prophylaxis can diminish the risk of neonatal GBS disease.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Although the majority of pregnant women remain asymptomatic, GBS colonization has been linked to certain obstetric complications, including chorioamnionitis and premature rupture of membranes. 4,5 Vertical transmission of maternal GBS is a leading cause of neonatal sepsis, pneumonia, and meningitis. Randomized clinical trials in the 1980s showed that intrapartum antibiotic prophylaxis can diminish the risk of neonatal GBS disease.…”
Section: Introductionmentioning
confidence: 99%
“…Infection of newborns exhibiting early-onset neonatal disease occurs via vertical transmission during passage through the birth canal or by exposure to infected amniotic fluid (1,17). Studies have correlated the incidence of early-onset neonatal disease as well as premature rupture of membranes with heavy GBS colonization of the vagina, cervix, and urine of pregnant women (1,10,11,13,15). A significant association has been shown between premature rupture of membranes and symptomatic early-onset neonatal disease (13,15).…”
mentioning
confidence: 99%
“…GBS colonized in pregnant woman may cause preterm birth act, EMR and PMR (26) . However, in certain studies, it is reported that risk of development of EMR and PMR are not increased by GBS colonization (7,27) . In our study no significant association was detected between GBS colonization and EMR and PMR.…”
Section: Discussionmentioning
confidence: 98%
“…Although GBS infection may be asymptomatic in pregnant women, it may be appeared as asymptomatic bacteriuria, cystitis, pyelonephritis, endometritis, wound infection after cesarean section or episiotomy, puerperal sepsis, meningitis and thrombophlebitis with serious complications such as preterm birth act, early membrane rupture (EMR), prolonged membrane rupture (PMR) and chorioamnionitis (7) . Since it may cause serious infections, it is necessary to define basic strategies to prevent and treat GBS infections.…”
Section: Introductionmentioning
confidence: 99%